(untitled) (The Pakistan Development Review, 2003)
Demand estimates for food not only provide information bases to characterise food demand structure, but also provide a complete and consistent framework to evaluate the impacts of policy changes, since both price policies and the human capital policies related to health and nutrition are closely related to the determination of expenditure (or income) elasticities. This study attempts to produce a complete set of expenditure and price elasticities based on the estimates of food demand parameters in Turkey. The Linear Expenditure System (LES) is estimated using the last available cross-section budget survey data. The estimates throw light on certain characteristics of Turkish household behaviour that has some consequences for government policies.